2006
DOI: 10.1002/jbm.b.30582
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of osteoblast‐like cell responses to calcium silicate and tricalcium phosphate ceramics in vitro

Abstract: Calcium silicate ceramics have been proposed as new bone repair biomaterials, since they have proved to be bioactive, degradable, and biocompatible. ␤-tricalcium phosphate ceramic is a well-known degradable material for bone repair. This study compared the effects of CaSiO 3 (␣-, and ␤-CaSiO 3 ) and ␤-Ca 3 (PO 4 ) 2 (␤-TCP) ceramics on the early stages of rat osteoblast-like cell attachment, proliferation, and differentiation. Osteoblast-like cells were cultured directly on CaSiO 3 (␣-, and ␤-CaSiO 3 ) and ␤-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
134
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(139 citation statements)
references
References 35 publications
3
134
2
Order By: Relevance
“…In addition, CS offers improved bioactivity compared with that of calcium phosphate materials. 18,19 In our previous study, 25 an apatite layer was formed on the n-CS/PEEK composite, and the entire surface of this specimen was nearly covered with a thick and compact apatite layer after immersion for 28 days. We predicted that apatite would form on the surface of n-CS/ PEEK in the early implantation period, and then, the bone matrix would integrate with the apatite.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…In addition, CS offers improved bioactivity compared with that of calcium phosphate materials. 18,19 In our previous study, 25 an apatite layer was formed on the n-CS/PEEK composite, and the entire surface of this specimen was nearly covered with a thick and compact apatite layer after immersion for 28 days. We predicted that apatite would form on the surface of n-CS/ PEEK in the early implantation period, and then, the bone matrix would integrate with the apatite.…”
mentioning
confidence: 71%
“…11 Some studies have proved that CS is biocompatible, biodegradable, and bioactive, with the ability to stimulate proliferation and osteogenic differentiation of osteoblasts, [12][13][14][15][16] and CS has been shown to have higher bioactivity than calcium phosphate materials. [17][18][19] Abu Bakar et al 20 prepared 20 volume% (vol%) HA-reinforced PEEK composite (HA/PEEK) with a porosity of 60% and pore size ranging from 300 to 600 mm using a leaching of particulate technique employing a suitable pore-forming agent, and these materials were implanted into the distal metaphyseal femur of pigs to evaluate the biological responses and tissue ingrowth of the material. Histological studies revealed the presence of fibrovascular tissue within the pores after 6 weeks and mature bone formation after 16 weeks, indicating that the HA/PEEK composite exhibited favorable osseointegration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies reported that ion dissolution products (Si and Ca in particular) of CaO -SiO 2 -based bioactive materials stimulate osteoblast proliferation and differentiation [18 -20,53]. Ni et al [53] demonstrated that cell attachment, proliferation of osteoblast-like cells and the expression level of ALP activity were greater on the surface of CaSiO 3 ceramics than on b-TCP ceramics. The key determining factor for these differences is thought to be the Si ions and the higher amount of Ca ions released from CaSiO 3 ceramics than b-TCP ceramics [53].…”
Section: Discussionmentioning
confidence: 99%
“…They include calcium phosphate ceramics [1][2][3][4], hydroxyapatite (HA) ceramic [5][6], bioactive glass (BG) [7][8][9][10] and calcium phosphate cements (CPC) [11][12][13][14][15]. Some of these materials have been used in the clinic with excellent results [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%